2013
DOI: 10.1098/rspb.2013.1024
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in neotropical wet forests during the Cenozoic is linked more to atmospheric CO 2 than temperature

Abstract: Department of Biology, Wesleyan University, Middletown, CT 06459, USA Models generally predict a response in species richness to climate, but strong climate-diversity associations are seldom observed in long-term (more than 10 6 years) fossil records. Moreover, fossil studies rarely distinguish between the effects of atmospheric CO 2 and temperature, which limits their ability to identify the causal controls on biodiversity. Plants are excellent organisms for testing climate-diversity hypotheses owing to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
(107 reference statements)
0
12
0
Order By: Relevance
“…This appears to contradict the concept of an explosive radiation of angiosperms in a declining [CO 2 ], cooling world (Supplemental Fig. S1, A and B; Royer and Chernoff, 2013). Royer and Chernoff (2013) suggested that, although within-group species richness should positively correlate with [CO 2 ] levels, large physiological differences across groups could result in a group outcompeting others under declining [CO 2 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This appears to contradict the concept of an explosive radiation of angiosperms in a declining [CO 2 ], cooling world (Supplemental Fig. S1, A and B; Royer and Chernoff, 2013). Royer and Chernoff (2013) suggested that, although within-group species richness should positively correlate with [CO 2 ] levels, large physiological differences across groups could result in a group outcompeting others under declining [CO 2 ].…”
Section: Discussionmentioning
confidence: 97%
“…Royer and Chernoff (2013) suggested that, although within-group species richness should positively correlate with [CO 2 ] levels, large physiological differences across groups could result in a group outcompeting others under declining [CO 2 ]. Our results lend support to the hypothesis of Royer and Chernoff (2013), as they hint at a mechanistic basis for the previously reported photosynthetic advantages of angiosperms in a low-[CO 2 ] world and the photosynthetic toll on gymnosperms under the same conditions Nackley et al, 2018). However, further species sampling within and between evolutionary groups is required to test the robustness of our idealized paleosimulations.…”
Section: Discussionmentioning
confidence: 99%
“…The vegetative biology of angiosperms is often treated as end members on a physiological continuum shared by other vascular plants and as if angiosperm advantages can be neutralized under the right environmental conditions, such as greatly elevated levels of atmospheric CO 2 , with other plants being elevated to comparably high levels of productivity [3,9,[17][18][19]. Alternatively, the angiosperms can be viewed as presenting fundamentally new ecological strategies founded upon novel physiological innovations enabling uniquely high growth rates [2,6,13,20,21]. The results presented here support the view that angiosperm physiology-at least among more derived angiosperms-is fundamentally distinct.…”
Section: Discussion (A) Limits On the Ecological Possibilities Of Fermentioning
confidence: 99%
“…There is no clear consensus on the deep-time evolution of photosynthesis in vascular plants from studies using proxy estimates from fossil leaves (26, 96,102) or model estimates derived from fossil leaf traits (54). Similarly, there remains a wide range of opinions on the evolution of the productivity of terrestrial ecosystems through time and whether modern systems are the most productive (24, 25) or less so than those of the geological past (such as the Eocene), assuming a positive correlation between diversity and productivity (77,130). What is clear, however, is that the total area of forested ecosystems expands dramatically poleward during greenhouse intervals (Figures 1 and 2), which on evolutionary timescales enabled a greater speciation rate during the Cenophytic era and likely higher productivity in many biomes because of a species-area effect (77).…”
Section: Paleobotanical Insights On Co 2 Fertilization Of Photosynthesismentioning
confidence: 99%